Non-extraction Orthodontic Treatment with Molar Distalization - Malik, Vikas; Yadav, Puneet; Grover, Seema; Chaudhary, Girish (Journal of Orofacial Research, 2012)
A case report of 16 years female who reported to department with chief complaint of irregularly placed front teeth and an unpleasant smile. Patient was diagnosed with class II div 2 malocclusion with arch length discrepancy of 8.5 mm in maxilla with buccally placed maxillary canines. Molar distalization technique was planned using pendulum appliance. Molars were distalized by 5 mm in the right, 6 mm in left maxillary arch. Crowding was relieved effectively utilizing space created by molar distalization. Class I molar and canine relation was achieved and maxillary arch was aligned in 7 months.